The crisis of modern sport and the dimension of achievement for its conquest - Sekine, M.; Hata, T. (International Journal of Sport & Health Science, 2004)
The necessity of recognising an ideological basis for overcoming the crisis of modern sport symbolised by doping is set out in this paper. The first part provides the consideration of the influences which doping brings to sport. The second section examines a means for conquering the crisis of sport. The third and final section considers the dimension of achievement, which is different from excellence, and proposes the ideological basis for conquering the crisis of modern sport based on the development of a new sports culture, different from modern sport in its quality, is proposed.